Deriving Functional Hepatocytes from Pluripotent Stem Cells. (1st August 2014) - Szkolnicka, Dagmara; Farnworth, Sarah L.; Lucendo‐Villarin, Baltasar; Hay, David C.
Abstract: Despite major progress in the management of human liver disease, the only cure for a critically failing organ is liver transplantation. While a highly successful approach, the use of cadaveric organs as a routine treatment option is severely limited by organ availability. Therefore, the use of cell‐based therapies has been explored to provide support for the failing liver. In addition to developing new treatments, there is also an imperative to develop better human models 'in a dish'. Such approaches will undoubtedly lead to a better understanding of the disease process, offering new treatment or preventative strategies. With both approaches in mind, we have developed robust hepatocyte differentiation methodologies for use with pluripotent stem cells. Importantly, our procedure is highly efficient (∼90%) and delivers active, drug‐inducible, and predictive human hepatocyte populations. Curr. Protoc. Stem Cell Biol . 30:1G.5.1‐1G.5.12. © 2014 by John Wiley & Sons, Inc.